Folk Mahabharath Part-2 - (:unkn) unknown (My University, 2022)
The folk Mahabharath has its own uniqueness. A folk poet sustains his imagination through the tale. He connected the lines one by one. He did not woven the whole tale in one go. The epic stretches over lines and truly deserves to be called Mahakavya. One man has sung all these lines and Dr.PK Rajshekhar has taken it all down making the audio recording simultaneously. It is an amazing feat in Kannada. No one had given the reason why Bhism had to lie on the bed of arrows. The folk Mahabharatha has filled the gap through the Chameleons episode. How chameleons cursed Bhim and on the battlefield, he got the bed of arrows. It is an indication of folk belief that even the animals must be respected. Compassion for all creatures is imperative according to the folk poet. Communal harmony is the idea of the poet singer. Poet narrates the situation when Dushyasana pealed Draupadi’s robe and that sweem into Bhima’s ken. Poet described an Abimanyu as a half-a-leaf. The folk poet said that all become one in paradise.
Keywords: Folk Mahabharath Part-2; Folk Poet; P.K. Rajashekar; Bhishma cursed by a chameleon; Bandrabahu killed by Bheema; Kannada